Durable Efficacy of Dolutegravir Plus Lamivudine in Antiretroviral Treatment–Naive Adults With HIV-1 Infection: 96-Week Results From the GEMINI-1 and GEMINI-2 Randomized Clinical Trials. (1st March 2020) - Cahn, Pedro; Madero, Juan Sierra; Arribas, José R.; Antinori, Andrea; Ortiz, Roberto; Clarke, Amanda E.; Hung, Chien-Ching; Rockstroh, Jürgen K.; Girard, Pierre-Marie; Sievers, Jörg; Man, Choy Y.; Urbaityte, Rimgaile; et al.
Abstract : Background: The 2-drug regimen dolutegravir + lamivudine was noninferior to dolutegravir + tenofovir disoproxil fumarate/emtricitabine in achieving HIV-1 RNA <50 copies/mL in treatment-naive adults in the 48-week primary analysis of the GEMINI trials. We present results from the prespecified 96-week secondary analyses. Setting: One hundred eighty-seven centers in 21 countries. Methods: GEMINI-1 and GEMINI-2 are identical, double-blind phase III studies. Participants with screening HIV-1 RNA ⩽500, 000 copies/mL were randomized 1:1 to once-daily dolutegravir + lamivudine or dolutegravir + tenofovir disoproxil fumarate/emtricitabine. Results: At week 96, dolutegravir + lamivudine (N = 716) was noninferior to dolutegravir + tenofovir disoproxil fumarate/emtricitabine (N = 717) in achieving HIV-1 RNA <50 copies/mL (Snapshot algorithm; −10% noninferiority margin) in the pooled analysis (proportion of responders, 86.0% vs 89.5%, respectively; adjusted treatment difference [95% CI], −3.4% [−6.7 to 0.0007]), GEMINI-1 (−4.9% [−9.8 to 0.03]), and GEMINI-2 (−1.8% [−6.4 to 2.7]). Proportions of participants in the HIV-1 RNA ≥50 copies/mL Snapshot category were largely unchanged from week 48 to 96. Eleven participants taking dolutegravir + lamivudine and 7 taking dolutegravir + tenofovir disoproxil fumarate/emtricitabine met confirmed virologic withdrawal criteria through week 96; none had treatment-emergent resistance mutations. Dolutegravir + lamivudine had a lower rate of drug-related adverse events than dolutegravir + tenofovir disoproxil fumarate/emtricitabine (19.6% vs 25.0%; relative risk ratio, 0.78; 95% CI: 0.64 to 0.95). Renal and bone biomarker changes favored dolutegravir + lamivudine. Conclusions: Consistent with 48-week data, dolutegravir + lamivudine demonstrated long-term, noninferior efficacy vs dolutegravir + tenofovir disoproxil fumarate/emtricitabine without increased risk of treatment-emergent resistance, supporting its use in treatment-naive HIV-1–infected individuals. Abstract : Supplemental Digital Content is Available in the Text.